Derivácia funkcie

9000063303

Časť: 
C
Derivácia funkcie \(f\colon y = \sqrt{\sin x}\) je rovná:
\(f'(x) = \frac{\cos x} {2\sqrt{\sin x}},\ x\in \mathop{\mathop{\bigcup }}\nolimits _{k\in \mathbb{Z}}\left (2k\pi ;\pi + 2k\pi \right )\)
\(f'(x) = \frac{\sin x} {2\sqrt{\cos x}},\ x\in \mathop{\mathop{\bigcup }}\nolimits _{k\in \mathbb{Z}}\left (2k\pi ; \frac{\pi } {2} + 2k\pi \right )\)
\(f'(x) = \frac{1} {2\sqrt{\sin x}},\ x\in \mathop{\mathop{\bigcup }}\nolimits _{k\in \mathbb{Z}}\left (2k\pi ;\pi + 2k\pi \right )\)
\(f'(x) = \frac{\cos x} {2\sqrt{\sin x}},\ x\in \mathop{\mathop{\bigcup }}\nolimits _{k\in \mathbb{Z}}\left \langle 2k\pi ; \frac{\pi } {2} + 2k\pi \right \rangle \)

9000063305

Časť: 
C
Derivácia funkcie \(f\colon y = \sqrt{\frac{x-1} {x+1}}\) je rovná:
\(f'(x) = \frac{1} {(x+1)^{2}} \sqrt{\frac{x+1} {x-1}},\ x\in (-\infty ;-1)\cup (1;\infty )\)
\(f'(x) = \frac{\sqrt{x-1}} {(x-1)^{2}\sqrt{x+1}},\ x\in (-\infty ;-1)\cup \langle 1;\infty )\)
\(f'(x) = \frac{x-1} {2\sqrt{(x+1)^{3}}} ,\ x\neq - 1\)
\(f'(x) = \frac{x-1} {\sqrt{(x+1)^{3}}} ,\ x\in (-\infty ;-1)\cup \langle 1;\infty )\)

9000063101

Časť: 
B
Derivácia funkcie \(f\colon y = \frac{x^{2}-1} {x^{2}+1}\) je rovná:
\(f'(x) = \frac{4x} {(x^{2}+1)^{2}} ,\ x\in \mathbb{R}\)
\(f'(x) = \frac{-4x} {x^{2}+1},\ x\in \mathbb{R}\)
\(f'(x) = \frac{4x^{3}} {(x^{2}+1)^{2}} ,\ x\in \mathbb{R}\)
\(f'(x) = \frac{4x} {x^{2}+1},\ x\in \mathbb{R}\)

9000063103

Časť: 
B
Derivácia funkcie \(f\colon y = \frac{x^{2}-x} {x+1} \) je rovná:
\(f'(x) = \frac{x^{2}+2x-1} {(x+1)^{2}} ,\ x\neq - 1\)
\(f'(x) = 2x - 1,\ x\neq - 1\)
\(f'(x) = \frac{x^{2}+2x-1} {(x+1)^{2}} ,\ x\neq 0\)
\(f'(x) = \frac{2x} {(x^{2}+1)^{2}} ,\ x\neq 0\)

9000063104

Časť: 
B
Derivácia funkcie \(f\colon y = \frac{\sin x} {\sin x-\cos x}\) je rovná:
\(f'(x) = \frac{-1} {(\sin x-\cos x)^{2}} ,\ x\neq \frac{\pi }{4} + k\pi ;k\in \mathbb{Z}\)
\(f'(x) = \frac{\sin ^{2}x-\cos ^{2}x} {(\sin x-\cos x)^{2}} ,\ x\neq \frac{\pi }{4} + k\pi ;k\in \mathbb{Z}\)
\(f'(x) = \frac{\sin x(\cos x+1)} {(\sin x-\cos x)^{2}} ,\ x\neq \frac{\pi }{4} + k\pi ;k\in \mathbb{Z}\)
\(f'(x) = \frac{\cos ^{2}x-\sin ^{2}x} {(\sin x-\cos x)^{2}} ,\ x\neq \frac{\pi }{4} + k\pi ;k\in \mathbb{Z}\)

9000063107

Časť: 
B
Derivácia funkcie \(f\colon y =\cos x(1 +\sin x)\) je rovná:
\(f'(x) =\cos ^{2}x -\sin ^{2}x -\sin x,\ x\in \mathbb{R}\)
\(f'(x) = -\sin x\cos x,\ x\in \mathbb{R}\)
\(f'(x) =\cos x,\ x\in \mathbb{R}\)
\(f'(x) =\sin x +\sin ^{2}x -\cos ^{2}x,\ x\in \mathbb{R}\)

9000063109

Časť: 
B
Derivácie funkcie \(f\colon y = 3^{x}\cdot x^{3}\) je rovná:
\(f'(x) = 3^{x}x^{2}(x\ln 3 + 3),\ x\in \mathbb{R}\)
\(f'(x) = 3^{x+1}x^{2}\ln 3,\ x\in \mathbb{R}\)
\(f'(x) = 3^{x}x^{2}(x + 3),\ x\in \mathbb{R}\)
\(f'(x) = 3^{x}x^{2}(x\ln x + 3),\ x\in \mathbb{R}^{+}\)